2019
DOI: 10.1080/02813432.2019.1569424
|View full text |Cite|
|
Sign up to set email alerts
|

Women’s perspectives on the management and consequences of hyperemesis gravidarum – a descriptive interview study

Abstract: Objective: Hyperemesis gravidarum (HG) affects 0.3–3% of pregnant women and is a leading cause of hospitalization in early pregnancy. The aim of the study was to investigate women’s treatment and management of HG, as well as the consequences of HG on women’s daily life. Design and setting: A cross-sectional study based on a structured telephone interview and an online questionnaire. Participants were recruited by social media and by the Norwegian patient’s organization for HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 28 publications
0
48
1
7
Order By: Relevance
“…While adverse pregnancy outcomes of HG are conflicting and the current study findings revealed no association of the condition with an increased risk of fetal or maternal outcomes compared to the control pregnancies, it should be noted that HG has been associated with a significant psychosocial burden in women together with an adverse impact on daily activities 22 in addition to increased risk of low quality of life negatively affecting the acceptance of pregnancy and the role of motherhood 23 . This seems notable given the reported lack of support from healthcare professionals and suboptimal management of women with HG 22 .…”
Section: Adverse Pregnancy Outcomes N (%) Preterm Deliverycontrasting
confidence: 68%
“…While adverse pregnancy outcomes of HG are conflicting and the current study findings revealed no association of the condition with an increased risk of fetal or maternal outcomes compared to the control pregnancies, it should be noted that HG has been associated with a significant psychosocial burden in women together with an adverse impact on daily activities 22 in addition to increased risk of low quality of life negatively affecting the acceptance of pregnancy and the role of motherhood 23 . This seems notable given the reported lack of support from healthcare professionals and suboptimal management of women with HG 22 .…”
Section: Adverse Pregnancy Outcomes N (%) Preterm Deliverycontrasting
confidence: 68%
“…The term "morning sickness" may also be misleading because the symptoms often are present throughout the day. Although the symptoms usually resolve spontaneously by gestational week 16, from 5 to 10% of women experience prolonged symptoms, sometimes throughout the entire pregnancy [6]. Early recognition of NVP and initiation of optimal management are essential and may prevent further complications, such as dehydration, ketonuria, excessive weight loss, malnutrition, and in worst cases, the diagnosis of hyperemesis gravidarum [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperemesis gravidarum (HG) is a severe subtype of nausea and vomiting in pregnancy (NVP) that is estimated to affect 0.3–2% of pregnancies [ 1 , 2 ]. It is a common reason for admission to the hospital in the first trimester of pregnancy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperemesis gravidarum (HG) is a severe subtype of nausea and vomiting in pregnancy (NVP) that is estimated to affect 0.3–2% of pregnancies [ 1 , 2 ]. It is a common reason for admission to the hospital in the first trimester of pregnancy [ 2 ]. HG typically begins in the first trimester of pregnancy, likely due to increasing amounts of hormones, and usually ends in the second trimester, although some cases have lasted the entire duration of pregnancy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation